2020
DOI: 10.1007/1345_2020_98
|View full text |Cite
|
Sign up to set email alerts
|

Status of IGS Reprocessing Activities at GFZ

Abstract: Based on a large network of continuously operated GNSS tracking stations the International GNSS Service (IGS) has a valuable contribution for the realization of the International Terrestrial Reference System (ITRS). In order to contribute to its next realization, the IGS is preparing for a new reprocessing of the GNSS data from 1994 to 2020 including GPS, GLONASS, and – for the first time – Galileo. A first test campaign including single- and multi-system solutions for 2017 and 2018 was performed to derive con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

6
3

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…For GLONASS, large positive offsets are observed for R855, R856, R858 of the block M+ with 36, 27, and 33 mm and for block M satellite R857 with 39 mm. This behavior can also be noted in the preliminary GFZ repro3 results presented in Männel et al [2020a] and the analysis of the experimental ACC combination shown in Sośnica et al [2020]. Meanwhile, the lowest value of the standard deviation for GLONASS is obtained for R802 (K1B) with 15 mm and the highest for R730 (M) with 47 mm.…”
Section: Pp Frghsupporting
confidence: 69%
“…For GLONASS, large positive offsets are observed for R855, R856, R858 of the block M+ with 36, 27, and 33 mm and for block M satellite R857 with 39 mm. This behavior can also be noted in the preliminary GFZ repro3 results presented in Männel et al [2020a] and the analysis of the experimental ACC combination shown in Sośnica et al [2020]. Meanwhile, the lowest value of the standard deviation for GLONASS is obtained for R802 (K1B) with 15 mm and the highest for R730 (M) with 47 mm.…”
Section: Pp Frghsupporting
confidence: 69%
“…We considered only GPS observations since most of the stations recorded only this constellation during most of the period considered. The orbits and clock offset products have been generated beforehand by the GFZ Analysis Center in preparation of the IGS Repro3 campaign (Männel et al 2020). These products are consistent with ITRF2014 (Altamimi et al 2016).…”
Section: Processingmentioning
confidence: 99%
“…This assumption was tested by processing GPS and Galileo solutions independently in the framework of the next IGS reprocessing campaign (repro3). However, due to the different satellite PCOs used (z-PCO GPS from igs14.atx and z-PCO GAL from GSA) a terrestrial scale bias of 1.16 ± 0.27 ppb (part per billion) was observed in the GFZ submission (Männel et al 2020). When taking this terrestrial scale into account, GPS and Galileobased coordinates agree on the level of a few millimeters in the height component.…”
Section: Methods I: Galileo With Calibrated Antenna Offsetsmentioning
confidence: 99%